2012
DOI: 10.17221/115/2012-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Physical methods of resveratrol induction in grapes and grape products - a review

Abstract: Tříska J., Houška M. (2012): Physical methods of resveratrol induction in grapes and grape products -a review. Czech J. Food Sci., 30: 489-502.Trans-resveratrol ((E)-3,4',5-trihydroxystilbene) is a substance that is produced by a large number of plants as a phytoalexin and has a wide range of beneficial biological properties. Resveratrol has been credited as being potentially responsible for the "French paradox" -the observation that the French have a relatively low incidence of coronary heart disease, even th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 45 publications
0
8
0
1
Order By: Relevance
“…14 Interestingly, UV irradiation and ozonization of grapes have been shown to increase the content of resveratrol endogenously in wine products and grape juice (reviewed in Ref. 15). …”
Section: Grape and Whole-grape Products For Better Healthmentioning
confidence: 99%
“…14 Interestingly, UV irradiation and ozonization of grapes have been shown to increase the content of resveratrol endogenously in wine products and grape juice (reviewed in Ref. 15). …”
Section: Grape and Whole-grape Products For Better Healthmentioning
confidence: 99%
“…Accumulation of antifungal substance(s) under red-light radiation was shown to be the active response to fungal attack in a study by Islam et al (1998). Additionally, trans-resveratrol content varied widely following UV irradiation depending on grape variety, degree of maturity, storage period, and treatment method in plants (Tříska and Houška (2012). Furthermore, Demkura and Ballaré (2012) reported that UVR8 plays a key role in mediating the effects of UV-B radiation on pathogenicity by controlling expression of the sinapate biosynthetic pathway.…”
Section: Discussionmentioning
confidence: 97%
“…Because of the poor bioavailability of resveratrol, it may be useful, especially for cancer chemoprevention, if resveratrol content could be increased in diets. To this end, recently multiple methods have been studied in an attempt to increase the content of resveratrol endogenously in wine products and grape juices using UV irradiation and/or ozonisation of grapes (reviewed in [34]). These types of studies are important as high-resveratrol containing diets would allow an increase in the daily resveratrol intake of individuals.…”
Section: Resveratrol’s Metabolites Derivatives and Reformulationsmentioning
confidence: 99%